Effect of latitude on maize kernel weight and grain yield across China. (24th February 2021) - Baloch, Nazia; Liu, Wanmao; Hou, Peng; Ming, Bo; Xie, Ruizhi; Wang, Keru; Liu, Yuee; Li, Shaokun
Abstract: Latitude influences maize kernel weight (KW) and grain yield by variation in climatic conditions such as temperature and solar radiation. In this study, the major aim is to examine the spatial variation in 1, 000‐KW and grain yield of the same maize hybrids and to further understand the differences in the response of 1, 000‐KW and maize grain yield to climatic factors under a wide range of latitude. For this purpose, we conducted field experiments at 17 different locations in the North maize region (NM) and Huanghuaihai maize region (HM) of China between 33°35′ N and 46°48′ N latitude from 2013 to 2016. The extensively used five maize hybrids (Xianyu 335, Zhengdan 958, Denghai 11, Nonghua 101, and Zhongdan 909) in China were chosen for these experiments. Based on the findings of this study, the maize 1, 000‐kernel weight and yield were found to be significantly influenced by the latitude. The maximum average grain yield of five hybrids was observed (12.25 Mg ha –1 ) at 43°58′ N latitude. Whereas the maximum 1, 000‐KW of five hybrids was weighted (362.08 g) at the latitude of 41°48′ N, respectively. Five hybrids showed similar trends with latitudes. Among all the climatic factors, mean minimum temperature ( T m ) and accumulated solar radiation ( R a ) were mainly responsible for the variations of 1, 000‐KW and maize grain yield. Based on the obtained results of this research, it was also found that Xianyu 335 had higher yield potential, especially at high latitude. Core Ideas: This study was to examine the spatial variation in 1, 000 kernel weight and grain yield. Significant differences existed between cultivars and latitude in 1, 000 kernel weight and yield. Solar radiations was the main climatic factor affecting kernel weight and yield. At higher latitude, appropriate maize cultivar is recommended with high and stable yield.